Introducing a Cat Tool to Translate: Wordfast - Fika Apriliana; Ardiyarso Kurniawan; Sandy Ferianda; Fidelis Chosa Kastuhandani (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
This article aims at introducing CAT tools to those prospective translators who are familiar with with the tools for the first time. Some of the CAT tools must be paid for while some others are free. This article is to inform the readers about the list of free and paid CAT tools, advantages and disadvantages of those tools. One does not need special training for using a free CAT tool while using the paid CAT tools, one needs some special preparation. This article is going to focus more on Wordfast Pro as the second most widely used CAT tools after SDLTrados. Wordfast Pro is a paid software the functioning of which is based on the creation of a Translation Memory which facilitates and speeds up the translator's work. This article is going to briefly explain the advantages of Wordfast Pro and the steps of using it. The translation example is presented to reveal the different translation results of Wordfast Pro as a paid CAT tool and OmegaT as a free CAT tool. Therefore, the article will facilitate those who intend to know more about Wordfast Pro and start using it.